Pectoral Fin Morphometry of Nile Tilapia (Oreochromis niloticus) Cultivated in Different Aerator and Filter (Biosaintifika: Journal of Biology & Biology Education, 2022)
The anomaly of the pectoral fin is caused by an inappropriate amount of oxygen and ammonia within the water, which is expected to be resolved by the combination usage of an aerator and filter. This study aimed to analyze the combination usage of an aerator and filter with different amounts toward the growth of Nile tilapia’s pectoral fin. This study used a 2×2 factorial completely randomized design consisting of 4 treatments (ANF, AANF, AF, and AAF) with 6 replications. The measurement variable of the pectoral fin includes length, width, weight, and the ratio of the pectoral fin’s length with the total size of the fish. The measurement was analyzed using two way-ANOVA and continued with the LSD test. The results of the combination usage of the aerator and filter revealed a significant effect (P0.05) on the pectoral fin length, pectoral fin width, pectoral fin weight, and ratio of pectoral fin length to total body length. The research’s conclusion was the combination of usage aerator and filter had a positive impact on the growth of Nile tilapia’s pectoral fin. The study’s novelty is the combination usage of an aerator and filter with a different number to promote the growth of the cell within the pectoral fin of Nile tilapia. This research would benefit people through the discovery of the combination usage of an aerator and filter to improve the growth of Nile tilapia’s pectoral fin.